5x+8-6x-9=6x-7x-4

Simple and best practice solution for 5x+8-6x-9=6x-7x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+8-6x-9=6x-7x-4 equation:


Simplifying
5x + 8 + -6x + -9 = 6x + -7x + -4

Reorder the terms:
8 + -9 + 5x + -6x = 6x + -7x + -4

Combine like terms: 8 + -9 = -1
-1 + 5x + -6x = 6x + -7x + -4

Combine like terms: 5x + -6x = -1x
-1 + -1x = 6x + -7x + -4

Reorder the terms:
-1 + -1x = -4 + 6x + -7x

Combine like terms: 6x + -7x = -1x
-1 + -1x = -4 + -1x

Add 'x' to each side of the equation.
-1 + -1x + x = -4 + -1x + x

Combine like terms: -1x + x = 0
-1 + 0 = -4 + -1x + x
-1 = -4 + -1x + x

Combine like terms: -1x + x = 0
-1 = -4 + 0
-1 = -4

Solving
-1 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (7x+8)(7x^2+5x+8)= | | 9+2x=7(x+2)-6(x-3) | | 3t-8=4t+24 | | -(3-m)=-(7m+3) | | -(x+6)+7=9x+1-10x | | 18+2y-4=9y-14-3y | | 3(x+2)=9x+5-6x+1 | | (5x+4)(6x^2+3x+6)= | | -64+24=-4x+14x | | 1.4x-4.8=0.8x-0.9 | | (x+1)2-36=0 | | -2x+8+3x=-20+8 | | 13-6(x+3)=12-5(x+4) | | n(n+2)=399 | | w-8=0 | | 3.00(20+x)= | | 9x-(3x+30)=12 | | 23+2y-9=11y-14-5Y | | 105n=-140n | | .17(1.2)= | | 4(a-2)=3a | | 22-7x=111 | | -3(t-1)+6t=5t-1 | | 3(x-4)=8x-5-5x | | 7x+2-x=5+5x-2 | | -6x^2-10=0 | | 6x+4=4(x+3) | | -3x+5+4x=-5+22 | | 10=-6x^2 | | 6-4y=11-8y+4y | | 4x^7+6x^2=0 | | 20x-6=50x+12 |

Equations solver categories